Performance of BFRP Retrofitted RCC Piles Subjected to Axial Loads - Anandakumar Ramaswamy; Selvamony Chachithanantham; Seeni Arumugam (Advances in Materials Science and Engineering)
This paper deals with the behaviour of basalt fibre reinforced polymer (BFRP) composites retrofitted RCC piles subjected to axial compression loads. Currently the awareness of using FRP increases rapidly in engineering fields and also among public. Retrofitting becomes vital for aged and damaged concrete structures, piles, and so forth, to improve its load carrying capacity and to extend the service life. The load carrying capacity of piles retrofitted with basalt unidirectional fabric was studied experimentally. 15 nos. of RCC end bearing pile elements were cast with same reinforcement for axial compression experiment. Three piles were used as conventional elements, another 3 piles were used as double BFRP wrapped pile elements, and remaining 9 piles were used as retrofitted piles with BFRP double wrapping after preloaded to 30%, 60%, and 90% of ultimate load of conventional element. The effects of retrofitting of RCC pile elements were observed and a mathematical prediction was developed for calculation of retrofitting strength. The stress vs. strain relationship curve, load vs. deformation curve, preloaded elements strength losses are tabulated and plotted. Besides, crack patterns of conventional elements and tearing BFRP wrapped elements were also observed. The BFRP wrapped elements and retrofitted elements withstand more axial compressive load than the conventional elements.